Tata Kelola Korporasi, Pengungkapan Lingkungan, dan Nilai Perusahaan - Alwan Sri Kustono (Universitas Jember, 2016)
Firm value is a part that has been determined by a company after going through a process of activities for several years. This study was conducted to examine the relationship between the influence of corporate governance mechanisms and environmental disclosure on firm value. This research is a quantitative approach that aims to examine and analyze the effect of corporate governance mechanisms and environmental performance on firm value. Data is collected from financial statements and annual reports published by mining sector companies listed on the Indonesia Stock Exchange 2012-2014. There are five hypothesis that examined. The result show managerial ownership has a positive effect on firm value. Institutional ownership has a positive effect on firm value. Board of Commissioners shows a positive effect on the value of the company. Audit committee show that the audit committee has no effect on firm value. Environmental disclosure has no influence on firm value. This disclosure will have the confidence of investors that will affect the firm value. Keywords: institutional ownership, firm value, board of commissioners, audit committee, environmental disclosure